2016
DOI: 10.1016/j.cell.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Disordered Proteins Drive Emergence and Inheritance of Biological Traits

Abstract: Summary Prions are a paradigm-shifting mechanism of inheritance in which phenotypes are encoded by self-templating protein conformations rather than nucleic acids. Here we examine the breadth of protein-based inheritance across the yeast proteome by assessing the ability of nearly every open reading frame (∼5,300 ORFs) to induce heritable traits. Transient overexpression of nearly 50 proteins created traits that remained heritable long after their expression returned to normal. These traits were beneficial, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
232
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(253 citation statements)
references
References 75 publications
(116 reference statements)
5
232
0
1
Order By: Relevance
“…For example, in yeast both prion-like- proteins, and transient expression of non-prion proteins, have been shown to convey inheritance of traits independent of DNA. 26,27 In multicellular organisms, such as the nematode Caenorhabditis elegans, the RNA interference (RNAi) pathway results in non–DNA sequence–based heritable changes and environmental exposures can result in heritable phenotypic changes. 28 In mammalian models such as mice, a number of different types of non-genetic intergenerational or transgenerational inheritance have been observed.…”
Section: What Mediates Cross-generational Effects? (Genetics Shared mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in yeast both prion-like- proteins, and transient expression of non-prion proteins, have been shown to convey inheritance of traits independent of DNA. 26,27 In multicellular organisms, such as the nematode Caenorhabditis elegans, the RNA interference (RNAi) pathway results in non–DNA sequence–based heritable changes and environmental exposures can result in heritable phenotypic changes. 28 In mammalian models such as mice, a number of different types of non-genetic intergenerational or transgenerational inheritance have been observed.…”
Section: What Mediates Cross-generational Effects? (Genetics Shared mentioning
confidence: 99%
“…28 In mammalian models such as mice, a number of different types of non-genetic intergenerational or transgenerational inheritance have been observed. 26,27 The most well-known examples being heritable non-genetic changes in expression of specific loci, such as at the Agouti viable yellow ( Avy ) locus affecting coat color and metabolic outcome, caused by methylation silencing of an insertional mutation that results in ectopic agouti expression, 29 which can be modified by maternal diet. 30 In another example, Manikkam et al demonstrated transgenerational inheritance of adult onset disease from exposure of gestating mice to an endocrine disruptor - the pesticide Methoxychlor.…”
Section: What Mediates Cross-generational Effects? (Genetics Shared mentioning
confidence: 99%
“…For example, a number of studies have shown that genes involved in chromatin regulation and transcriptional repression uncover large amounts of cryptic variation when perturbed [7,2527] and that prions [2830] and proteins with regions of intrinsic disorder [31] can behave in a similar manner to Hsp90. Moreover, many genes buffer the effects of environmental variation; these genes might also modify the effects of genetic variation [32].…”
Section: Questions Regarding Hsp90 and Other Global Modifiersmentioning
confidence: 99%
“…IDPs also participate in higher order phenomena, such as regulation of the cell division cycle (10)(11)(12), circadian rhythmicity (13,14), and phenotypic plasticity (15,16). Recent evidence suggests that several IDPs can act in a prion-like manner to create protein-based molecular memories that drive the emergence and inheritance of biological traits (17), further emphasizing their importance in state (or phenotype) switching. Moreover, if overexpressed, IDPs have the potential to engage in multiple "promiscuous" interactions with other proteins, which can lead to changes in phenotype and pathological states (18,19).…”
mentioning
confidence: 99%